Diagnosis and Management of Kidney Stones Require a Patient-Centered Approach - Lederman, Lynne (MD Conference Express, 2015)
The prevalence of kidney stones has been increasing over time. A patient-centered approach to diagnosis and management of kidney stones includes correct interpretation of 24-hour urine samples, selection of dietary and pharmacologic interventions based on their risk/benefit profile, and recognition of rare genetic forms of kidney stones. This article discusses the epidemiology of kidney stones, interpretation of 24-hour urine chemistries to inform clinical practice, approaches to calcium phosphate stones and staghorn calculi, and conditions that can be associated with nephrolithiasis.